Optimization Medium Composition for Vitamin K2 by Flavobacterium sp. using Response Surface Methodology and Addition of Arachis hypogaea - Tan,Mu (2016)
ABSTRACT The purpose of this research was to enhance the production of vitamin K2 by fermentation optimization and Arachis hypogaea supplementation in Flavobacterium sp. mutant SP-L-01. Optimized culture condition were as follows: 6-days shake-flask culture at 37oC with initial pH value 7.0 ± 0.2, shaking speed in 120 r/min and medium volume of 30 mL with 2% inoculums. After optimization of fermentation medium by response surface methodology (RSM), optimized medium were maltose 23.8 g/l, glucose 9.69 g/l, beef extract 15 g/l, K2HPO4 4.5 g/l，NaCl 3.0 g/l and MgSO4·7H2O 0.3 g/l. Production of vitamin K2 after optimization reached to 10.97 mg/l, which is 79.25% higher than that before optimization (6.12 mg/l). 3 mg/mL of arachis hypogaea was added into the medium at 72 h of shake-flake cultivation, which improved the production of menaquinone-4 (MK4) up to 371% and menaquinone-6 (MK6) up to 149% higher than those of the original medium. D-(+)-catechin, one of the components of arachis hypogaea, was added alone into the medium, which also improved the vitamin K2 synthesis.